Effects of baclofen on swallow motor pattern - Fielder, Nathan W.; Frazure, Michael; Poliacek, Ivan; Bolser, Donald C.; Iceman, Kimberly E.; Pitts, Teresa (Frontiers in Neurology, 2025)
Baclofen is a GABAB receptor agonist used clinically to manage spasticity. It has also been associated with increased duration of mechanical ventilation and rates of aspiration pneumonitis. We hypothesized that baclofen would impair pharyngeal swallow, a vital airway protective reflex. Electromyography (EMG) activity was recorded in four spontaneously breathing, sodium pentobarbital-anesthetized cats. Swallow was stimulated by oral water infusion before and after administration of 3 μg/kg and 10 μg/kg (±)baclofen doses. Swallow-related thyrohyoid EMG amplitude increased after 3 μg/kg and 10 μg/kg (±)baclofen, while parasternal EMG amplitude decreased after 3 μg/kg (±)baclofen. Geniohyoid, thyroarytenoid, and thyropharyngeus EMG amplitudes increased on average, but did not reach significance. Clinically, increased thyrohyoid activation may extend duration of laryngeal abduction. Decreased parasternal activation could impair development of the negative intrathoracic pressure that aids bolus propulsion during swallow. These changes may reflect increased risk of aspiration, and more work is needed to study the effects of baclofen on airway protection.